Analysis of aggregates and particles in protein pharmaceuticals - Mahler, Hanns-Christian; Jiskoot, Wim (John Wiley & Sons, 2012)
This book describes how to address the analysis of aggregates and particles in protein pharmaceuticals, provides a comprehensive overview of current methods and integrated approaches used to quantify and characterize aggregates and particles, and discusses regulatory requirements. Analytical methods covered in the book include separation, light scattering, microscopy, and spectroscopy.